The development of an employee value proposition framework for the South African water board sector - Ndoyisile A. Theys; Emmerentia N. Barkhuizen (SA Journal of Human Resource Management, 2022)
Orientation: The South African water board sector plays an essential role in providing water and basic sanitary needs to the country. Yet the sector faces drastic talent shortages required to deliver its service mandate.